CONSTANT CURVATURE FACTORABLE SURFACES IN 3-DIMENSIONAL ISOTROPIC SPACE - Aydin, Muhittin Evren (Korean Mathematical Soc, 2018)
In the present paper, we study and classify factorable surfaces in a 3-dimensional isotropic space with constant isotropic Gaussian (K) and mean curvature (H). We provide a non-existence result relating to such surfaces satisfying H/K - const. Several examples are also illustrated.
Keywords: isotropic space; factorable surface; isotropic mean curvature; isotropic Gaussian curvature